Divergent thinking and mathematics achievement in Turkey: Findings from the programme for international student achievement (PISA-2003) - Unal, Hasan; Demir, Ibrahim (ELSEVIER SCIENCE BV, 2009)
The purpose of this study was to examine divergent thinking on achievement in four areas of mathematics (geometry, arithmetic, algebra, statistics and probability). The sample consisted of 4545, 15-years old Turkish students whom participated in the PISA-2003 study. The participants completed a questionnaire and participated in mathematics test. ANOVA and MANOVA was used to identify differences if any among divergent thinker vs. non-divergent thinkers in four areas of mathematics. Results from this study indicate that divergent thinking ability plays an important role in achievement in mathematics. (C) 2009 Elsevier Ltd. All rights reserved
Keywords: divergent thinking; geometry; creativity; Pisa 2003; Education & Educational Research